End-user development third international symposium, IS-EUD 2011, Torre Canne (BR), Italy, June 7-10, 2011. proceedings - Costabile, Maria Francesca; Dittrich, Yvonne; Fischer, Gerhard; Piccinno, Antonio (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the Third International Symposium on End-User Development, IS-EUD 2011, held in Torre Canne, Italy, in June 2011. The 14 long papers and 21 short papers presented were carefully reviewed and selected for inclusion in the book. In addition the volume contains 2 keynote speeches, 14 doctoral consortia, and information on 3 workshops. The contributions are organized in topical sections on mashups, frameworks, users as co-designers, infrastructures, methodologies and guidelines, beyond the desktop, end-user development in the workplace, meta-design, and supporting end-user developers.